2016
DOI: 10.7759/cureus.580
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Prostate Cancer Treatment Information on Cancer Center Websites

Abstract: IntroductionCancer center websites are trusted sources of internet information about treatment options for prostate cancer. The quality of information on these websites is unknown. The objective of this study was to evaluate the quality of information on cancer center websites addressing prostate cancer treatment options, outcomes, and toxicity.Materials and methodsWe evaluated the websites of all National Cancer Institute-designated cancer centers to determine if sufficient information was provided to address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…If confirmed, this association also might serve as friendly predictor of website accuracy for users with no medical background. Generally, the findings of this study are consistent with many other studies investigating the quality of online information about various medical conditions, both on the Romanian internet [11][12][13][14][15] as well as on the English, Spanish or other language websites [16][17][18][19][20][21][22][23][24][25][26]. With a few exceptions, most of the authors have reported modest completeness and accuracy scores but, it should be noted the heterogeneity of methodologies and evaluation tools applied in these studies prevents a rigorous comparison.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…If confirmed, this association also might serve as friendly predictor of website accuracy for users with no medical background. Generally, the findings of this study are consistent with many other studies investigating the quality of online information about various medical conditions, both on the Romanian internet [11][12][13][14][15] as well as on the English, Spanish or other language websites [16][17][18][19][20][21][22][23][24][25][26]. With a few exceptions, most of the authors have reported modest completeness and accuracy scores but, it should be noted the heterogeneity of methodologies and evaluation tools applied in these studies prevents a rigorous comparison.…”
Section: Discussionsupporting
confidence: 89%
“…ANOVA test or t-test for independent samples were used as comparison tests for all data with normal distribution. All statistical analyses were performed in SPSS v. 22. The cut-off value for statistical significance was set at α = 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…A prior study showed that even among the websites of NCI-designated cancer centers, only a minority had sufficient information to answer 11 validated decision-specific knowledge questions about early PCa treatment. [16] These findings suggest a gap in available information for shared decision-making about PCa treatment options, particularly AS for which multiple different testing protocols are used. [13]…”
Section: Discussionmentioning
confidence: 99%
“…The problem is underlined by previous research showing that even on health-care provider websites, the quality of information is not always adequate and may sometimes be directly misleading. 3 …”
Section: Introductionmentioning
confidence: 99%